Nanay, Ate at Yaya sexual and reproductive risks and decision-making experiences of domestic helpers in Maasin City, Southern Leyte - Gonzalez, Jana Felice P.
The study explOred how domestic helpers make reproductive decisions and practice their sexual and reproductive rights, including the freedom from sexual risks. The experiences of domestic helpers from (1) dating, entering romantic relationships and marriage, (2) fertility intentions, family planning and childrearing, and (3) potential risk for sexual harassment and abuse were chronicled. Their understanding of sexual and reproductive rights and their perception of the notion of ?control over one?s body? were also probed. This study is guided by the feminist standpoint theory of Sandra Harding that emphasized the significance of reflexivity and social position in knowledge production, as well as the claims of Correa and Techesky of rights as social entitlement. The data collection made use of semi-structured interview schedules to reveal the respondent?s experiences and perceptions. Focus group discussions and in-depth interviews schedules were participated in by thirty six helpers of reproductive age employed in Maasin City, Sdouthern Leyte. Eighteen employers of domestic helpers were also interviewed. The results showed that unlike in the Western concept of ?:control over one?s body?, helpers? choicers are interwoven with social factors. Helpers reconcile their choices with the implied societal expectations apparent in both employment and own household domains. Helpers also face the risk of harassment and abuse in employment and own household domains. Helpers also face the risk of harassment and abuse in employment due to their subordinate status and shared personal spaces with employers. These risks are also present in their own household context, stemming from gender power relations in the family. Largely, the helpers? axperiences emphasized that cultural stereotypes and patriarchal dominance continue to persist.